Corporate Social Responsibility - Business Opportunity or Obligation for Georgian Companies (European Journal of Marketing and Economics, 2023)
CSR is a relatively new concept for Georgia. Its history is not even two decades old, and the development process is taking place at a slow pace. In recent years, the concept of social responsibility has been more or less accepted by large businesses. From unsystematic CSR measures companies are slowly moving to a strategic approach, although their social initiatives are mainly focused on increasing the well-being of vulnerable groups of society. On the one hand, this is due to the insufficient level of awareness of CSR in the business sector, and on the other hand, the limited expectations of society because the public's perception of CSR is mainly related to charity. The paper presents an analysis of the modern trends in the development of CSR in Georgia using qualitative and quantitative secondary data. It is based on the works and studies of various scientists. Qualitative analysis, namely statistical and thematic analysis methods are used as the method of analysis.
Keywords: corporate social responsibility, business strategy, altruistic responsibility, business opportunity, competitive advantage, sustainable development